Evaluation of the entrustable professional activities (EPAs) of the population health promoter domain by North Dakota pharmacists - David M. Scott; Michael E. Kelsch; Anqing Zhang; Daniel L. Friesner (Centro de Investigaciones y Publicaciones Farmaceuticas, 2020)
Objective. Entrustable Professional Activities (EPAs) are a list of professional tasks (with associated competency ratings) that pharmacy educational organizations support, and accreditation organizations require, for assessment by colleges and schools of pharmacy. This manuscript assesses the perceived frequency of performing EPAs in the population health promoter (PHP) domain among pharmacists practicing in North Dakota. Methods. This survey assessed the self-reported EPA activities (inclusive of the PHP domain) of registered pharmacists living and practicing in North Dakota. There were 990 pharmacists surveyed, and 457 (46.1%) of pharmacists responded. Results. Within the PHP domain, pharmacists reported performing "Minimize adverse drug events and medication errors" most frequently (mean=3.4, SD=2.0), followed by "Ensure that patients have been immunized against vaccine-preventable diseases" (mean=2.3, SD 2.3), "Maximize the appropriate use of medications in a population" (mean=2.2, SD 2.3), and "Identify patients at risk for prevalent diseases in a population" (mean=1.3, SD=1.9). In these Core EPAs PHP domains, the clinical pharmacists reported the highest level, followed by pharmacy managers and staff pharmacists. Conclusion. Pharmacists in North Dakota reported that EPAs in the PHP domain are practiced regularly. Thus, EPAs in the PHP domain have potential as a means to assess outcomes in pharmacy education and practice.